Educators' experiences and perceptions of school violence : an analysis of causes, triggers and the rile of racism. - Gouveia, Carla Samantha Garrido De (My University, 2011)
School violence is a pervasive social phenomenon within the global and South African context. Many factors are implicated in its genesis. Representations of such incidents in the media are racially described, with the violence seeming to occur between racialothers. This qualitative research report was informed by the completion of questionnaires by fifteen educators employed at large, co-educational high schools in the broader Johannesburg area. Thematic Content Analysis was used to explore the data which emerged. These findings suggest that school violence is a complex phenomenon which is difficult to define clearly. The school as the site of violence appears to be a critical part of the definition suggesting that youth violence in other domains does not elicit the same concern as violence within the school context. This may be linked to the school’s function as a site of socialisation. All educators in the sample have observed or been informed of incidents of school violence within their school contexts, predominantly of the learner-on-learner type. Incidents range in both severity and frequency, with a multiplicity of perceived causes and triggers being identified. Educators identified the home as the primary site of the genesis of such violence, with school being described as a space which teaches and demonstrates multiculturalism and integration. Educators were divided with regards to the role of racism. Racism was either perceived as a scapegoat or as a genuine cause of violence, although the existence of racism within the school context was not denied. The impact of the violence on school functioning and the importance of intervention were all highlighted by the educators. Educators favoured a zero tolerance approach to school violence, with the option of expulsion being advocated for, which may indicate limited systemic understanding of school violence. Educators expressed that school violence was sensationalised in the media, and did not accurately represent the reality at all South African schools. Educators felt that at their schools, at least, violence was under control.